High levels of circulating cell‐free DNA are a biomarker of active SLE. (23rd August 2018) - Xu, Yalan; Song, Yijun; Chang, Jiazhen; Zhou, Xiya; Qi, Qingwei; Tian, Xinping; Li, Mengtao; Zeng, Xiaofeng; Xu, Mengnan; Zhang, Wenjuan; Cram, David S; Liu, Juntao
Abstract: Background: High levels of circulating cell‐free DNA (cfDNA) have been reported in patients with inflammatory conditions. The aim of the study was to investigate the levels of cfDNA in patients with systemic lupus erythematosus (SLE). Materials and methods: Comparative groups comprised 22 nonpregnant and 36 pregnant women with SLE (test groups) and 60 nonpregnant and 199 pregnant women with no history of SLE (control groups). The levels of cfDNA in plasma were quantitated by a fluorometric dsDNA assay. Results: Compared to controls, the median levels of cfDNA were significantly higher in nonpregnant SLE patients (7.38 ng/mL vs 4.6 ng/mL, P = 0.033) and in pregnant SLE patients (7.65 ng/mL vs 5.25 ng/mL, P = 0.003). Based on SLE disease activity index (SLEDAI) scores, the median cfDNA levels were significantly higher in patients with active disease (4 < SLEDAI < 15) compared with patients with inactive disease (SLEDAI < 4) (13.58 ng/mL vs 6.72 ng/mL, P = 0.01). While there was a trend of increased cfDNA levels with higher SLEDAI scores ( R 2 = 0.3, P < 0.001), we found no association of increased cfDNA levels with nephritis, skin manifestations, multiorgan inflammations or with other inflammatory markers such as decreased C3 and C4 levels or increased anti‐ds DNA antibodies. Conclusions: Our results suggest that in addition to classical SLE serological markers, measurement of circulating plasma cfDNA levels has potential as a useful biomarker for assessing SLE disease activity in patients and monitoring treatment.